The Concept of Corporate Criminal Liability in the Indonesian Criminal Law System - Saipudin, Lalu; HS., Salim; Rodliyah, Rodliyah; Wulandari, Laely (Magister of Law, Faculty of Law, University of Mataram, 2025)
The development of corporations as main actors in economic activities brings significant impacts, both positive and negative on society and the environment. The phenomenon of corporate crime that harms the state, the public, and the environment drives the urgency of reforming corporate criminal liability in the Indonesian criminal law system. This study conceptually examines corporate criminal liability through a normative juridical and comparative approach, analyzing doctrines of criminal liability such as strict liability and vicarious liability (Article 37 of Indonesia’s new Criminal Code), as well as exploring the development of other liability models like corporate culture, identification theory, and management failure, which are relevant for application in Indonesian Criminal Law. In Indonesia’s new Criminal Code (KUHP), the recognition of corporations as criminal law subjects and their criminal liability is regulated under Articles 45 to 49, although normative problems persist concerning fault boundaries, structural relationships, criteria, and limitations of criminal liability. The study’s findings indicate that corporate punishment demands a legal system that is adaptive, and accountable, and considers organizational structure and internal corporate culture while upholding the principles of justice and proportionality in criminal law. By adopting contemporary theories and strengthening norms in sectoral laws, the corporate criminal liability system is expected to be able to provide deterrent effects and more effective protection for public interests.